There will be one solution. To solve that:
1. Get the y alone by switching the places.
6x+y=2 > y=2-6x
-18x+3y=12 > 3y=12-18x > Then divide 3 on each number > y=4-6x
After doing that, you can solve this in graphing or algebra way.
Ima do the algebra way:
SO we have 2 system of equations. Now pick one equestion.
I will pick, y=2-6x. Now Ima replace the Y with the other equation y=4-6x >
4-6x=2-6x.
Now solve. And get > 0 aka Infinite Solution.
Y = - pie/4
y = -0.785
I'm not sure if I'm right so u might wanna make sure
Answer is = X^6
Please give me the brainliest
Hey! Your answer would be = 6ab+15ac
Answer:
x > -99/4
Step-by-step explanation:
I must assume that you meant (-2/5)x -9<9/10.
This inequality has 3 terms. The LCD is 10. Multiply each term by 10 and reduce the result:
10(-2/5)x - 10(9) < 10(9/10), or:
-4x - 90 < 9
Adding 90 to both sides results in:
-4x < 99
Here we must divide by a negative number (that is, by -4). This requires reversing the direction of the inequality sign:
x > -99/4 is the final solution.